2021
DOI: 10.1590/0001-3765202120200945
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights in bacterial vaginosis etiology through genomic approaches

Abstract: Bacterial vaginosis (BV) has been considered as dysbiosis state whose etiology is not fully understood. This condition affects a large number of women of reproductive age and its study has been highly relevant due to the growing association of BV with and gynecological and obstetric complications and diseases, in addition to a greater susceptibility to sexually transmitted diseases, including HIV. The vaginal microbiota composition presents high variability among different ethnic groups of women, although, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Since the prevalence of BV is not the same in different patient populations despite having similar exposures, and due to the higher incidence in patients of African descent, genetic studies have been performed and revealed specific genetic loci implying a role for biological pathways related to cell signaling and mucosal immunity in the pathogenesis of BV [66]. For example, a genome-wide associated study that included women from Kenya identified an association of genes encoding for molecules involved in innate immunity, such as Toll-like receptors (TLRs), interleukin-8, TIRAP, MYD88, with specific microorganisms involved in the pathogenesis of BV [67].…”
Section: Epidemiology Risk Factors and Pathophysiology Of Bvmentioning
confidence: 99%
“…Since the prevalence of BV is not the same in different patient populations despite having similar exposures, and due to the higher incidence in patients of African descent, genetic studies have been performed and revealed specific genetic loci implying a role for biological pathways related to cell signaling and mucosal immunity in the pathogenesis of BV [66]. For example, a genome-wide associated study that included women from Kenya identified an association of genes encoding for molecules involved in innate immunity, such as Toll-like receptors (TLRs), interleukin-8, TIRAP, MYD88, with specific microorganisms involved in the pathogenesis of BV [67].…”
Section: Epidemiology Risk Factors and Pathophysiology Of Bvmentioning
confidence: 99%
“…Bacterial communities undoubtedly exhibit a profound influence on the vaginal microbiome, with different ethnic groups exhibiting a high variability in vaginal microbiota composition. Genomics significantly contributes to the colonization and persistence of Lactobacillus strains but has some limitations [ 12 ]. Although the widespread presence and significance of Lactobacillus have already been widely reported, research progress remains hindered by the complexity and variability of vaginal microbiota.…”
Section: Introductionmentioning
confidence: 99%